234U/238U activity ratios in groundwaters from two aquifers in Saudi Arabia, and correlation with water chemistry. Issue 4 (October 2018) - El-Sharkawy, Ahmed M.
Abstract: The purpose of this study was to determine the activity concentrations of uranium isotopes ( 234 U and 238 U) and the 234 U/ 238 U activity ratios in groundwater wells from Saudi Arabia. These wells are located in two different regions and tapping different aquifers. The uranium isotopes were measured by alpha spectrometry. The uranium activity ratios ( 234 U/ 238 U) in the investigated samples had an average value of 1.38 and ranged from 1.0 to 2.17. The relationship between the activity concentrations of the combined uranium and the water chemical composition in the studied wells was also investigated. Good correlation was found with redox potential described by R 2 value of 0.74. Also, a good negative correlation was observed between The TDS content of the groundwater samples and the uranium activities described by R 2 value of 0.59. Finally, with twenty groundwater samples collected from two large areas, the presence of uranium isotopes in the Saq and Dammam aquifers can't be easy to judge but within the framework of this study, it can be concluded that the distribution of 238 U and 234 U in these two aquifers is more dependent on the mineralogical composition of the aquifer matrix and by the geochemical/hydrochemical conditions present. Highlights: Groundwater samples have to be analyzed for their uranium content. Radiochemical steps were utilized in the extraction of uranium from water. Quality assurance parameters were followed. The correlation between uranium activities and some groundwater chemical parameters was investigated.